2016
DOI: 10.1021/acs.jchemed.6b00395
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Implementation and Evaluation of Flipped Classes and Peer-Led Team Learning in General Chemistry

Abstract: The research-based pedagogical strategy of flipped classes has been shown to be effective for increasing student achievement and retention in postsecondary chemistry classes. The purpose of flipped classes is to move content delivery (e.g., lecture) outside of the classroom, freeing more face-to-face time for active learning strategies. The opportunity to engage in active learning with students can be a challenge for instructors of large classes (more than 100 students). Furthermore, there has been little disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…In large classes, PLTL has the strongest evidence base with five of seven studies reporting setting sizes greater than 200 and effect sizes ranging from 0.02 to 0.84. This matches the scalability of PLTL where larger class sizes can be accommodated by increasing the number of peer leaders supporting implementation (Robert et al, ). Future research on the effectiveness of POGIL, PBL and collaborative learning in large classes and PLTL in small classes is still needed and could also include qualitative investigations into how class size influences the implementation of these approaches.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In large classes, PLTL has the strongest evidence base with five of seven studies reporting setting sizes greater than 200 and effect sizes ranging from 0.02 to 0.84. This matches the scalability of PLTL where larger class sizes can be accommodated by increasing the number of peer leaders supporting implementation (Robert et al, ). Future research on the effectiveness of POGIL, PBL and collaborative learning in large classes and PLTL in small classes is still needed and could also include qualitative investigations into how class size influences the implementation of these approaches.…”
Section: Discussionsupporting
confidence: 58%
“…To explore this hypothesis, a content review of the eight studies reporting setting sizes greater than 400 was conducted. Five studies (Eichler & Peeples, ; He, ; Lewis, ; Robert et al, ; Tien, Roth, & Kampmeier, ) used peer leaders or teaching assistants to facilitate interactions within large classes. Of the remaining three studies, two reported class sizes of approximately 100 students (Baepler et al, ; Casadonte, ) and the remaining study (Talanquer & Pollard, ) a class size of 250 students.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no doubt about the effectiveness of flipped learning in education of general and organic chemistry [8,10,[13][14][15][16]. What is less evident, as there are only a few studies [17,18], is if analytical chemistry is well suited to the flipped teaching Provides a deep understanding of material 9 Encourages more reading outside face-to-face time 3…”
Section: Benefits Of Using Flipped Learning For Delivery Of Analyticamentioning
confidence: 99%
“…Class time then establishes an interactive learning environment where students engage in activities and problem-based learning that are instructor led [5]. Flipped learning has been widely applied in STEM subjects, notably in the delivery of physics, engineering, and mathematics [3,4,8], and its use in chemistry teaching is increasing, with various studies being published on the delivery of organic or general chemistry in this way [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%